ASUHAN KEPERAWATAN PADA BAYI BBLR DENGAN PENERAPAN TERAPI PIJAT BAYI TERHADAP PENINGKATAN BERAT BADAN BAYI PREMATUR DI RUANG PERINATOLOGI RSUD KABUPATEN TANGERANG - Nur Hafidiani; Ria Setia Sari (Yayasan Nusantara Hasana Berdikari, 2024)
One of the suport actions that mothers can give for a baby and prematurely is to use sensory stimulation techniques. In developed countries, the use of complementary medicine and infant stimulation is increasing, and massage is considered a complementary supportive measure for infants. This Scientific Writing Work aims to analyze the implementation of the application of infant massage therapy to premature baby weight increase in the Perinatology room of Tangerang Regency Hospital. Providing nursing care intervention to infants with the application of infant massage therapy to premature baby weight gain. Based on the case study in management patients, the results were found that there were changes in oxygenation status such as pulse, breathing, and temperature in patients before and after treatment.